2001
DOI: 10.2355/isijinternational.41.1473
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Analysis on Formation of Internal Cracks in Continuously Cast Slabs by Mathematical Models.

Abstract: The formation of internal cracks in continuously cast slabs is mainly attributed to the strain status and microsegregation near the solidifying front of the slabs. Based on this understanding, the effects of the strain status at solidifying front and the chemical composition of liquid steel on the internal cracks were studied using a strain analysis model and a microsegregation model developed in the present study. The tensile strains at the solidifying front caused by bulging, unbending, and misalignment of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 7 publications
2
35
0
1
Order By: Relevance
“…3 line 1 depicts the bulging strain along the caster with the aforementioned formulation. Left-hand-side (LHS) axis is used to present the bulging strain which is also presented by dashed line 2 with the means of another formulation (Han et al, 2001) which is presented by the following equations:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 line 1 depicts the bulging strain along the caster with the aforementioned formulation. Left-hand-side (LHS) axis is used to present the bulging strain which is also presented by dashed line 2 with the means of another formulation (Han et al, 2001) which is presented by the following equations:…”
Section: Resultsmentioning
confidence: 99%
“…In this way, the secondary dendrite arm spacing can be sufficiently computed with respect to carbon content and local cooling rates. In another study (Han et al, 2001), the formation of internal cracks in continuously cast slabs was mathematically analyzed with the implementation of a strain analysis model together with a microsegregation model. The equation of heat transfer was also numerically solved along the caster.…”
Section: Previous Work and Current Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal cracks were predicted by comparing the strain state at the solidifying front with experimental data based critical strains. 8,9) Wang et al had done analysis on the formation of internal cracks in continuous casting slabs. They concluded that the corresponding strain in the arc and horizontal segments does not exceed this critical value, so the solidification front in the straightening segments would be much easy to crack.…”
Section: Creep Straightening Technology Of Continuous Casting Slab Bamentioning
confidence: 99%
“…They conc1uded that, in order to prevent internaI cracking, casting machines should be designed and operated such that the total strain at each position in the strand is minimized. More recently, Han et al [170] developed mathematical models for strain analysis and microsegregation during continuous casting of slab. They showed that the interaction between deformation and segregation during solidification leads to internaI cracking 0 f slabs.…”
Section: __________________________________ 143mentioning
confidence: 99%